Analysis of 14 Patients With Congenital Nephrotic Syndrome - Chen, Yan; Zhang, Yanqin; Wang, Fang; Zhang, Hongwen; Zhong, Xuhui; Xiao, Huijie; Yao, Yong; Jiang, Yi; Ding, Jie; Hou, Xinlin (Frontiers in Pediatrics, 2019)
From January 1995 to May 2018, 14 cases of CNS were diagnosed in the Department of Pediatrics, Peking University First Hospital，the clinical data were retrospectively studied. Eight patients had undergone genetic testing, seven of them had NPHS1 mutations (Primary CNS) and one did not have mutation. Among the seven patents who had NPHS1 mutations, six of them died and 1 of them had proteinuria. Eight of the 14 patients had CMV infection, and anti-CMV therapy was given to 7 of them, the other patient was hospitalized in critically ill condition and died before anti-CMV therapy. Among the 7 patients who received anti-CMV therapy, proteinuria disappeared in 2 patients; 2 patients died; 2 patients were lost to follow up; I patient still have 3+ proteinuria. Three patients had both NPHS1 mutations and CMV infection. After anti-CMV therapy, proteinuria resolved in 1 patient but relapsed to 3+ status due to a new infection. The other two patients died. Among all the 14 patients, only 1 patient received a renal biopsy with a mesangial proliferative glomerulonephritis pathology, negative CMV inclusion body and CMV-DNA. In this study, genetic defect could play a primary role in CNS and CMV could play a secondary role. Primary CNS with NPHS1 mutations had poor prognosis. Primary CNS might be accompanied by CMV infection that responds poorly to antiviral treatment. Secondary CNS caused by CMV infection may be cured by using antiviral therapy. However, genetic analysis is necessary to exclude genetic defect.